Introduction (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2020)
This special issue of Periphērica, Image and Storytelling: New Approaches to Hispanic Cinema and Literature, features leading research by scholars of Hispanic cultures at the crossroads of literature, film, mind, and society. The collection showcases cutting-edge fields and themes including cognitive studies, affect studies, embodiment, and empathy, as well as new perspectives on adaptation, film typology, film teaching, gender, and genre. The research presented in this special issue underscores the excitement produced by crossing disciplinary boundaries in the study of verbal and visual narratives, moving beyond prevalent transnational approaches that do not sufficiently address key factors in the creation and reception of film narratives such as historical-sociological contexts, affective dynamics, psychological responses, and gender variables. The contributors include scholars whose professional and social relationships to the history, practices, and evolution of the moving image and new media vary widely, broaching a diversity of theories and methodologies and presenting readers with a comprehensive and innovative perspective on film art and the relationship between filmmakers, films, spectators, and contexts.